Stability and sustainability of the pension fund of the Republic of Uzbekistan ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The pension system plays a critical role in ensuring social stability and the welfare of the population. The budget of the Pension Fund of the Republic of Uzbekistan is a key element of this system, providing financial support to retirees and ensuring the stability of the pension system as a whole. The stability and resilience of the pension fund in the Republic of Uzbekistan play a pivotal role in ensuring the well-being of retirees and the long-term sustainability of the pension system. This article aims to explore the fundamental aspects that contribute to the stability and resilience of the pension fund in Uzbekistan and its significance for the country's future.